Gasto em educa????o e o diferencial de sal??rios por qualifica????o: elasticidade de substitui????o entre consumo e adimpl??ncia - Oliveira, Augusto Marques de Castro (2016)
This work includes two studies. The first refers to an infinite horizon model of educational level choice, in which we find that in the long term, a stable relationship between wages and spending on education. On the demand side, it is assessed the impact of the workers` skill premium on the relative demand of qualified workers in the Brazilian Federal States (UF's). An analogous analysis if performed for the country members of the European Union (EU). The second study considers a dynamic model with habit formation and infinite horizon in which the consumer is a borrower which decides her level of consumption, payment of her debt and the new loans contract. It is estimated the parameters of this model using data from the Brazilian credit market and analyzed the sensitivity of the variables at steady state with respect to shocks in the interest rate to evaluate the impacts of monetary policy on the Brazilian credit market.